TINJAUAN SOSIOLOGIS TENTANG FENOMENA BULLYING DAN KENAKALAN SISWA DI LINGKUNGAN SEKOLAH BERBASIS AGAMA - Komariya, Lailatul; Karimah, Milla; Basir Hanif, Ahmad; Khairul Anam, Rifqi (As-Sulthan Journal of Education, 2026)
The phenomenon of bullying and student delinquency in faith based schools in Indonesia has become an increasingly complex social issue. Religious schools, which are ideally centers for moral development, are not free from acts of bullying and deviant behavior among students. This study aims to analyze this phenomenon from a sociological perspective, focusing on the influence of social structure, religious culture, and social media on student behavior. The research employs a library research method with a qualitative approach, drawing data from relevant books, scientific journals, and academic articles. The findings reveal that the hierarchical social structure in religious schools reinforces power relations between senior and junior students, which often lead to acts of bullying. Furthermore, an exclusive religious culture fosters social stratification based on moral labeling, while social media serves as a new arena for performing religious identity, intensifying social pressure and symbolic competition among students. This study concludes that bullying and delinquency in religious schools are products of complex social interactions between religious values, social structures, and digital culture.